BISNIS MODEL STRATEGI PENGEMBANGAN BISNIS JASA PENGIRIMAN: STUDI PADA PERUSAHAAN JASA PENGIRIMAN DI JAKARTA - Sasongko, Agung Hari; Umar, Abdullah; Agusman, Glory; Sugiharto, Sugiharto (Lembaga Penerbitan Unversitas Esa Unggul, 2016)
AbstractThe purpose of this research is to determine business model strategy of a company in the future, how does a company offers more to customers and maintain customers and everything related with business development. Business development is something required to be done by every company in order to be able to compete. This matter also happens in delivery service business. Delivery service business in Indonesia is very popular in Indonesia, wherein online delivery service business develops continuously, so delivery services also increase. But, this development must be followed by business model development, so the result will be satisfying for delivery service companies, especially in Jakarta. Research result shows that the best strategy is market penetration. Some alternatives that can be done are by enhancing resources by alliancy and coopetition, creating a competitive price scheme by mapping the cost from partner to obtain the best price, and also by doing promotion through several medias owned by the company, by ATL or BTL with the main purpose to increase selling.Â Keywords: Business Model, Courier Service.